Bank Infaq: Tinjauan Kritis Perspektif Fiqh Muamalah - Muhammad Maulana Hamzah; Erwandi Tarmizi Anwar (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2020)
Abstract Background: This study aims to examine the concept of Bank Infaq from Islamic Jurisprudence Perspective. Bank Infaq is an intermediate organization that organize the fund of charity to improve people’s prosperity using financing service. With short term, charity bank uses charity fund (tabarru’) as funding instrument and provides financing using single model contracts qordhul hasan. Method: This research uses phenomenology method and depth interview to capture the implementation of charity bank based on its operational procedure and normative descriptive is used to study muamalah and positive law related to contemporary practice above. The normative approach is carried out by reviewing sharia laws relating to the practice of charity Bank, especially in terms of sharia contracts. Result: The result shows for general charity bank has a good aim, concept and action to empower the low society using financial instrument, but its procedure still leave some issues in funding, amil’s right and financing. The result of this paper is not only describe and criticize the charity bank according to Islamic jurisprudence but also give some suggestions in sharia perspective to make it better and more barokah. Keywords: Bank Infaq; Funding; Tabarru’; Islamic Jurisprudence